(untitled) (Research, Society and Development, 2023)
Cervical cancer is the third most incident cancer among women in Brazil, being the second most incident in the North region and the first cause of mortality among women in the region (INCA 2022). requiring complementary treatments such as Hemodialysis. Considering these women as integral and holistic human beings, according to Wanda Horta, nursing theorist, with altered basic human needs in which they need to be assisted by nurses. In this way, the present study aims to identify in the non-gray scientific literature which basic human needs are affected in patients on hemodialysis and to identify patients with uterine cervix cancer on hemodialysis. Being a qualitative research of an integrative review with exploratory approach. (LILACS). Ten articles were found, divided into four categories: Basic Human Needs; Nursing diagnosis; nursing care and cervical cancer and hemodialysis. It is concluded that the study provides foundations that will help guide the approaches of future research and the practice of nursing care in hemodialysis based on Wanda Horta’s theory, and on the implementation of nursing systematization as well as studies on patients with cervical cancer in hemodialysis.